Quantitative Assessment of Labeling Probes for Super‐Resolution Microscopy Using Designer DNA Nanostructures. Issue 10 (4th May 2021) - Ganji, Mahipal; Schlichthaerle, Thomas; Eklund, Alexandra S.; Strauss, Sebastian; Jungmann, Ralf
Abstract: Improving labeling probes for state‐of‐the‐art super‐resolution microscopy is becoming of major importance. However, there is currently a lack of tools to quantitatively evaluate probe performance regarding efficiency, precision, and achievable resolution in an unbiased yet modular fashion. Herein, we introduce designer DNA origami structures combined with DNA‐PAINT to overcome this issue and evaluate labeling efficiency, precision, and quantification using antibodies and nanobodies as exemplary labeling probes. Whereas current assessment of binders is mostly qualitative, e. g. based on an expected staining pattern, we herein present a quantitative analysis platform of the antigen labeling efficiency and achievable resolution, allowing researchers to choose the best performing binder. The platform can furthermore be readily adapted for discovery and precise quantification of a large variety of additional labeling probes. Abstract : Probe performance : Using programmable, antigen‐decorated designer DNA origami nanostructures, performance of labeling probes, including antibodies and nanobodies, is tested. The platform reveals that primary‐secondary antibody labeling can only resolve antigens spaced down to 40 nm. The nanostructures enable performance evaluation of a multitude of labeling probes for super‐resolution microscopy.